Speech by the Honourable Chief Minister, Penang, at the St. George’s Girl School Annual Speech and Prize Giving Day to be held on Tuesday, 26th October 1976 at 9.00 a.m. - Lim, Chong Eu (1976)
I would like to thank the Chairman and Members of the Board of Governors and Headmistress for the honour they have shown to me by their kind invitation to address the school on the occasion of your Annual Speech and Prize Giving Day.